Development Of Union Fire Risk Assessment System For Manufacturing Industry - Muhammad Umar Azizi, Zulkhairul (2024)

(untitled)
The fire incidents in the manufacturing industry are very alarming. Fires in factory buildings can have a devastating impact on human lives, the environment, assets, and a company's reputation. There have been several studies showing that failure of maintenance works is the cause of fire incidents in the premises. This study focuses on the development of a Union Fire Risk Assessment (UFRA) system based on Hazard Identification, Risk Assessment, and Risk Control (HIRARC). The system has also been developed using the Microsoft Excel application. Furthermore, the system has been tested by several experts in the manufacturing industry to determine its usability and meet the specifications of the manufacturing industry. These experts have also conducted the System Usability Scale Test (SUS) and the system has scored 71 with a grade of C. This shows that the system is applicable and capable of use but needs to be improved in terms of several aspects before it can be expanded in the manufacturing industry. At the end of the study, the Union Fire Risk Assessment (UFRA) system was successfully developed but some improvements had to be made especially in the identification of maintenance work as there are several types of factory industries in our country. This ensures that more accurate contents can be incorporated into the Fire Risk Assessment Checklist.